ANALISIS PENGARUH PERTUMBUHAN ASET, STRUKTUR MODAL, UKURAN PERUSAHAAN, DAN NILAI PERUSAHAAN TERHADAP PROFITABILITAS PADA PT XYZ - Vaninda Agustina; Anita Handayani (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of conducting this research is to test the growth of assets, capital structure, company size and firm value which have an impact on profitability. The company that is the subject of this research is PT. XYZ. This type of research is a quantitative technique, where the research population is taken as many as 80 employees from a research sample of 100 employees of PT. XYZ. The data collection process was carried out using library research techniques and questionnaires. Analysis of the research data was carried out using validity tests, reliability tests, normality tests and multiple linear regression tests assisted by the SPSS ver. 22. The results of this study found that asset growth, capital structure, company size, and company value have a positive effect on profitability at PT. XYZ either partially or simultaneously. The result of the coefficient value of asset growth (X1) is 0.172 (17.2%), the result of the coefficient value of capital structure (X2) is 0.218 (21.8%), the result of the coefficient value of company size (X3) is 0.689 (68.9%) , and the results of the firm value coefficient (X4) are 0.138 (13.8%).